Experimental Study of Concrete Composites of Fly Ash and Ferronickel Slag for Gamma-Ray Shielding - Patrick Marcelino Wongso; Syamsir Dewang; Eko Budi Jumpeno; Okky Agassy Firmansyah; June Mellawati (BATAN, 2020)
This study aim is to determine the effect of partial replacement of cement by high percentages of fly ash and ferronickel slag as gamma radiation shielding properties of concrete. The percentages of replacement were 30% for fly ash and 10%, 20%, and 30% for ferronickel slag by weight of fine aggregate. Several physical parameters (linear attenuation coefficients, mass attenuation coefficients, half value layer, tenth value layer, mean free path, effective atomic number, and effective electron density) of concretes were measured using 600cc Thin Window Ionization Chamber. A broad beam transmission geometry method with 137Cs source was used for the radiation intensity measurements. The elemental compositions of the concretes were analyzed by using an energy dispersive X-ray Fluorescence Spectrometer (EDXRF). In this experiment, the concrete composite sample with composition of 0% fly ash and 30% ferronickel slag shows the most effective result in absorbing low energy gamma rays, therefore it has the potential as a candidate for gamma radiation shielding.